Compliance with Good Manufacturing Practices in feed production among feed producers in Uganda - Businge, Martha; Ahumuza, Ronnie; Waiswa, David; Kimuli, Emmanuel; Ssimbwa, David; Ssentumbwe, Peter; Kavuma, Peter; Lukuyu, Ben A. (International Livestock Research Institute, 2026)
This report presents the findings of an evaluation of compliance with Good Manufacturing Practices (GMP) among small and medium-scale livestock feed producers in Uganda. The study assessed the impact of a training and mentorship program implemented by the International Livestock Research Institute (ILRI) Uganda in collaboration with national partners that aimed to enhance feed quality and safety by strengthening producer capacity to apply GMP standards in daily operations.